Case Report: long-term clinical outcomes in RANBP2-associated acute necrotizing encephalopathy - Varghese, Sonia A.; Olubiyi, Olutayo I.; Basuroski, Irena Dujmovic; Broman-Fulks, Jordan; Cardwell, Emma B.; Peck, Stephanie; Yang, Qian-Zhou (JoJo); Hung, Sheng-Che; Hunter, Senyene E. (Frontiers in Pharmacology, 2025)
IntroductionAcute necrotizing encephalopathy (ANE) is a rare and severe neurological condition primarily affecting children and commonly triggered by viral infections. Morbidity and mortality rates are high. Pathogenic RAN-Binding Protein-2 (RANBP2) variants predispose children to recurrent ANE, known as ANE1, and increase the risk of severe outcomes and early death. Although the pathophysiology of ANE is not fully understood, an inflammation-mediated “cytokine storm” is believed to play a crucial role in central nervous system involvement. Currently, there is no guidance on the optimal duration of immunotherapy.Case presentationWe present a new pediatric case of RANBP2-associated ANE1, and update one previously published case, detailing their clinical characteristics, treatment strategies, and outcomes. Magnetic resonance imaging revealed lesions characteristic of ANE. In one patient, cerebrospinal fluid (CSF) analysis showed pleocytosis without evidence of bacterial or viral pathogens, and elevated CSF levels of interleukin-6 (IL-6) and IL-8 were consistent with neuroinflammatory response. Both patients experienced rapid neurological decline during ANE attacks. However, both patients were treated with timely immunotherapy, including steroids, plasma exchange, intravenous immunoglobulins, and tocilizumab, with favorable responses.ConclusionRecurrent ANE or ANE with a family history of severe neurological events in childhood should raise suspicion for RANBP2-associated ANE1. These cases emphasize the importance of early recognition, prompt immunotherapy initiation, and close monitoring in patients with ANE1. Our cases also contribute to the limited body of knowledge on neuroimaging, treatment, and outcomes in this rare condition, which is of great importance given that the optimal duration of immunotherapy in ANE1 is currently unknown.